EFEKTIVITAS PUPUK ORGANIK CAIR KULIT ARI KEDELAI UNTUK PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Shelli Aprilia Stanza Ardini; Rachmaniyah; Ferdian Akhmad Ferizqo (Poltekkes Kemenkes Surabaya, 2022)
One of the wastes of making tempe is soybean husk which comes from boiling and soaking. Soybean husk waste that is not utilized causes unpleasant odors and pollutes the environment. Utilization as organic fertilizer can be used to overcome the pollution. This study aims to utilize soybean husk waste as a liquid fertilizer applied to mustard greens (Brassica juncea L.). This type of research is included in the True Experimental Design. With the research design Pretest-Posttest Control Group Design. The object of this research is green mustard (Brassica juncea L.) as many as 30 samples and liquid organic fertilizer from soybean husk waste at concentrations of 5%, 10%, and 15% with 9 replications. The sampling technique used is Simple Random Sampling. Data were obtained from the field in the form of observations and measurements of mustard plant growth parameters including the height of the mustard plant, the number of leaves of the mustard plant, and the diameter of the stem of the mustard plant, the NPK content test in the laboratory, and data analysis was carried out with the Anova test. The application of liquid organic fertilizer from soybean husks did not significantly affect stem diameter and number of leaves, but did affect plant height. The effective concentration treatment on the growth of mustard greens is a 15% concentration treatment for plant height with an average of 35.85 cm. Liquid Organic Fertilizer of soybean epidermis with a concentration of 15% is effective on the growth of mustard greens. Suggestions for further researchers are to conduct research on other plants with higher concentrations in order to obtain optimal results on plant growth to be studied.